Aspects of the Swiss Labor Market - De Masi, Paula (IMF Working Papers; Working Paper ;, 1996)
This paper presents an analysis of the behavior of the Swiss labor market, which emphasizes both changes to labor supply and real wage inflexibility as determinants of recent unusually high levels of unemployment. Supply responses in the past meant that measured unemployment rates were rarely high. The paper suggests that these responses also meant that real wages were probably less responsive to shocks as a result. Econometric tests reported in the paper broadly confirm these suggestions, and imply that the level of unemployment consistent with stable inflation has risen in Switzerland.